2013
DOI: 10.1007/s00213-013-3249-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute electronic cigarette use: nicotine delivery and subjective effects in regular users

Abstract: Rationale Electronic cigarettes are becoming increasingly popular among smokers worldwide. Commonly reported reasons for use include: to quit smoking, avoid relapse, reduce urge to smoke, or as a perceived lower risk alternative to smoking. Few studies however, have explored whether e-cigarettes deliver measurable levels of nicotine to the blood.Objective This study in experienced users explores the effect of using an 18 mg/ml nicotine first generation e-cigarette on blood nicotine, tobacco withdrawal symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
174
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(196 citation statements)
references
References 26 publications
14
174
2
5
Order By: Relevance
“…This is perhaps not surprising given that almost all the studies of nicotine absorption from e-cigs suggest that they deliver markedly lower peak nicotine levels compared with cigarettes, and that they deliver nicotine more slowly than cigarettes, both of which are characteristics likely leading to less addiction. [21][22][23][24][25] We also found that users of more advanced e-cigs (in terms of size, battery power, ability to control timing of heat being applied to the coil, cost of e-cig, and so on), score higher on measures of dependence. This is also consistent with existing data, showing that advanced generation models deliver higher blood nicotine levels than current "cigalike" models.…”
Section: (234)mentioning
confidence: 68%
“…This is perhaps not surprising given that almost all the studies of nicotine absorption from e-cigs suggest that they deliver markedly lower peak nicotine levels compared with cigarettes, and that they deliver nicotine more slowly than cigarettes, both of which are characteristics likely leading to less addiction. [21][22][23][24][25] We also found that users of more advanced e-cigs (in terms of size, battery power, ability to control timing of heat being applied to the coil, cost of e-cig, and so on), score higher on measures of dependence. This is also consistent with existing data, showing that advanced generation models deliver higher blood nicotine levels than current "cigalike" models.…”
Section: (234)mentioning
confidence: 68%
“…Whether comparable reduction in urge to smoke/WS continue over a longer time period remains unclear. At this time point (10 mins after 10 puffs), although measurable nicotine levels from the e-cigarette will have reached the blood [13], blood nicotine levels are still likely to be rising and it may be that significant differences between groups might emerge after 20/30 minutes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Third generation devices bear little resemblance to cigarettes, use larger-capacity batteries, replacement heating coils and wicks for atomizers, and adjustable and programmable power delivery. Whilst early studies reported very little nicotine delivery from e-cigarettes [11,12], more recently, studies in experienced users have found measureable nicotine delivery (comparable to nicotine replacement therapy; NRT) [13,14] especially with newer generation devices [15]. E-cigarette use (often referred to as vaping) resembles the act of smoking: the user holds the device and draws on it like a cigarette; the aerosol produced resembles smoke and is drawn into the lungs and exhaled like smoke; tobacco (or menthol) flavouring mimics the taste of tobacco smoke and first generation devices resemble cigarettes exactly.…”
Section: Introductionmentioning
confidence: 99%
“…Though the mixture exiting the ECIG mouthpiece is commonly referred to as a "vapor," it is more correctly termed an "aerosol mist"-a system of liquid droplets suspended in a gas or gas mixture. 4 The apparent popularity of these products likely is attributable to a variety of factors, including marketing, 5 their availability in appealing flavors, 6,7 perceptions that they are less lethal than tobacco cigarettes, 8 and their ability to deliver nicotine, 9,10 a psychomotor stimulant that supports dependence. 11 Although some commentators speculate that ECIGs promise reduced tobacco-caused disease and death in cigarette smokers, 12,13 others speculate that daily, long-term use of these novel products imperils users with adverse health consequences, including nicotine dependence in individuals who were not nicotine-experienced prior to their ECIG use.…”
Section: Introductionmentioning
confidence: 99%
“…11,25 With ECIGs, differences in topography may help explain the fact that sometimes these products deliver nicotine and sometimes they do not. 9,10,16 Indeed, two studies have used observational methods to examine ECIG user puff topography, and both suggest that experienced ECIG users take longer puffs (e.g., approximately 4 s, on average) than tobacco cigarette smokers, approximately 2 s, on average. 26,27 In extreme cases, puff durations as long as 8 s have been observed.…”
Section: Introductionmentioning
confidence: 99%